Step-by-step explanation
then
![\begin{gathered} x\cdot y=A \\ x+y=B \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eb5jdukme69rykz5sryez63ql2oxwbs1uo.png)
Step 1
replace A and B
![\begin{gathered} x\cdot y=9\rightarrow\text{Equation (1)} \\ x+y=-6\rightarrow Equation(2) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/908xx8momd9obtzlzemo6so3xao0u7keb3.png)
solve for x and y,
isolate y in equation 2 and replace in equation (1)
![\begin{gathered} x+y=-6\rightarrow Equation(2) \\ x=-6-y \\ x\cdot y=9\rightarrow\text{Equation (1)} \\ (-6-y)y=9 \\ -6y-y^2-9=0 \\ y^2+6y+9=0 \\ (y+3)^2=0 \\ so,\text{ y=-3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kv1g13zlbqt9zfaxi1ptzefbwodywajiyj.png)
and replace in equation (1) to get x
![\begin{gathered} x\cdot y=9 \\ -3x=9 \\ x=(9)/(-3) \\ x=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1kdlrzwi4lewwiwp3ufv69rmr4aa9gskxu.png)
so, for the first X, the number are -3 and -3
Step 2
![\begin{gathered} x\cdot y=4 \\ x+y=4 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/65y141zn6nxyyyd2ksm8uhvzi0s0ibjsny.png)
isolate, x in the second equation and replace in the first one
![\begin{gathered} x+y=4 \\ x=4-y \\ \text{replace} \\ x\cdot y=4 \\ (4-y)y=4 \\ 4y-y^2-4=0 \\ -y^2+4y-4=0 \\ y^2-4y+4=0 \\ (y-2)^2=0 \\ y=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6zhgqu9djktsloq3108xskg6olgzizozk5.png)
replace in equation
![\begin{gathered} x+y=4 \\ x+2=4 \\ \text{subtract 2 in both sides} \\ x+2-2=4-2 \\ x=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4fuaxpzxj1k6wz1bdvzj8vfjwga7tlwlgo.png)
Hence, for the second X, the numbers are 2 and 2
using this method you will be abel to solve all the problems in that page
I hope this helps you